Marilyn Naidoo (ed.) 2021. Making Connections: : Integrative Theological Education in Africa. - Pali, Khamadi Joseph (Stellenbosch Theological Journal, 2024)
Theological education has a remarkable impact on the Christian leadership, mission, and other ministries of the congregations. Therefore, it is of utmost significance to regularly review theological discourse, curriculum, pedagogy, and institutional systems (pp. 4, 35). The book mentioned above is one of the seminal works edited by Prof Marilyn Naidoo concerning the development of theological education in Africa. It explores how integration within African theological education is understood and can be implemented by applying appropriate theological, philosophical, and pedagogical tools (pp. 4, 6).